Implementasi Data Mining Pada Hasil Penjualan Makanan Beku Menggunakan K Means Clustering - Nenna Irsa Syahputri; Siti Sundari; Rismayanti (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
Maintaining inventory stock so that there are no empty items is one way to maintain customer satisfaction. In today's competitive business world, we are required to always develop our business in order to survive in the competition, especially in sales competition, it requires entrepreneurs to find a pattern that can increase sales and marketing within the company, one of which is by utilizing sales data. Applying clustering data mining techniques so that it can help NCekma Frozen stores in determining strategies for determining frozen food stocks using the K Means algorithm.